Sistem Pendukung Keputusan Seleksi Penerimaan Karyawan Dengan Metode SAW - aris tantowi, akhmad; Inalawie, Reggie (Institut Informatika Dan Bisnis Darmajaya, 2025)
This research aims to develop a decision support system for employee recruitment at PT. Syifatech Tegalindo using the Simple Additive Weighting (SAW) method. The company's current recruitment process is still manual, often resulting in subjective decisions and inconsistent selection results. This study implemented the SAW method to provide objective and consistent recommendations for employee selection based on predetermined criteria including interviews, competency tests, academic grades, work experience, and personality. The system was developed using PHP and a MySQL database. Test results showed that the SAW method can provide accurate ranking recommendations for prospective employees compared to manual selection by Human Resources experts. Implementation of this system is expected to improve the quality of employee recruitment decisions and reduce the time required for the selection process..